Body Mapping to Explore Reproductive Ethno-Physiological Beliefs and Knowledge of Contraception in Timor-Leste. (June 2018) - Wallace, Heather Julie; McDonald, Susan; Belton, Suzanne; Miranda, Agueda Isolina; da Costa, Eurico; da Conceicao Matos, Livio; Henderson, Helen; Taft, Angela
Maternal mortality remains a significant public health challenge for Timor-Leste. Although access to quality family planning measures may greatly reduce such deaths, consideration of indigenous perceptions, and how they influence reproductive health decision-making and behavior, is crucial if health services are to provide initiatives that are accepted and helpful in improving reproductive health outcomes. We aimed to demonstrate that body mapping is an effective method to traverse language and culture to gain emic insights and indigenous worldviews. The authors' two qualitative research projects (2013 and 2015) used a decolonizing methodology in four districts of Timor-Leste, body mapping with 67 men and 40 women to illuminate ethno-physiology and indigenous beliefs about conception, reproduction, and contraception. Body mapping provided a beneficial conduit for identifying established indigenous reproductive perceptions, understandings, and vocabulary, plus fears surrounding contraception. This may inform health service provision and engagement, ultimately improving the reproductive health of community members.